A point mutation in gp91-phox of cytochrome b558 of the human NADPH oxidase leading to defective translocation of the cytosolic proteins p47-phox and p67-phox. - J H Leusen; M de Boer; B G Bolscher; P M Hilarius; R S Weening; H D Ochs; D Roos; A J Verhoeven (The Journal of Clinical Investigation, 1994)
The superoxide-forming NADPH oxidase of human phagocytes is composed of membrane-bound and cytosolic proteins which, upon cell activation, assemble on the plasma membrane to form the active enzyme. Patients suffering from chronic granulomatous disease (CGD) are defective in one of the following components: p47-phox and p67-phox, residing in the cytosol of resting phagocytes, and gp91-phox and p22-phox, constituting the membrane-bound cytochrome b558. In an X-linked CGD patient we identified a novel missense mutation predicting an Asp–>Gly substitution at residue 500 of gp91-phox, associated with normal amounts of nonfunctional cytochrome b558 in the patient's neutrophils. In PMA-stimulated neutrophils and in a cell-free translocation assay with neutrophil membranes and cytosol, the association of the cytosolic proteins p47-phox and p67-phox with the membrane fraction of the patient was strongly disturbed. Furthermore, a synthetic peptide mimicking domain 491-504 of gp91-phox inhibited NADPH oxidase activity in the cell-free assay (IC50 about 10 microM), and the translocation of p47-phox and p67-phox in the cell-free translocation assay. We conclude that residue 500 of gp91-phox resides in a region critical for stable binding of p47-phox and p67-phox. Images